The therapeutic potential of phiC31 integrase as a gene therapy system - Karow, Marisa; Calos, Michele P. (Expert Opinion on Biological Therapy, 2011)
Introduction: The φC31 integrase system is a phage-derived system that offers the ability to integrate plasmid DNA into the chromosomes at a subset of endogenous preferred locations associated with robust gene expression. Recent progress highlights the unique advantages of this system for in vivo gene therapy and for use in stem cells. Areas covered: The φC31 integrase system has been under development for ten years and has been demonstrated to be effective for integration of plasmids in a variety of tissues and organs for gene therapy in animal systems, as well as in isolated human cells. We focus on work with the φC31 integrase system during the past 12 18 months. This work has centered on a series of papers involving in vivo delivery of the integrase system to the liver and a variety of studies demonstrating the utility of the integrase system in stem cells. Expert opinion: We conclude that the φC31 integrase system has significant potential for liver gene therapy, if effective DNA delivery methods for large mammals become available. The φC31 integrase system displays an outstanding fit for use in pluripotent stem cells, and this area is expected to be the subject of intense development. © 2011 Informa UK, Ltd.
CRIS-Team Scopus Importer:2025-02-10
Keywords: Embryonic stem cells; Hemophilia; Induced pluripotent stem cells; Liver gene therapy; Phage integrase; Site-specific integration